Productivity improvement in the rice-wheat cropping system - Chatrath, Ravish; Singh, S K (Indian Farming, 2015)
A significant part of the future food demand has to come from ricewheat production systems and thus, it assumes special challenge as the yield of rice-wheat tends to plateau or decline in the northern plains of India. It is necessary to address the problems of rice-wheat system to keep the pace of production in tune to the future demand. Development of newer technologies in the form of advanced varieties suitable for heat stress, shorter maturity period and responsive to RCTs and their proper dissemination to the farmer’s level will be the key strategies for sustainability of rice wheat cropping system.